(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
The structure is governed by ch arge-assisted N⁺–H•••Cl cation-anion hydrogen bonds that permit alternation between organic/inorganic layers[1]. The intermolecular interactions were investigated using Hirshfeld surface analysis[2-3]. The thermal behavior of (I) was also discussed using TGA/DTA, which showed the thermal stability of the compound up to 190°C. The DFT calculations have been performed using the B3LYP method at the LANL2DZ level. For the new hybrid compound, we have also measured the value of the electronic part of the third-order nonlinear optical susceptibility using the third harmonic generation (THG) method at 1064 nm[4-5].